1978
DOI: 10.1080/00288233.1978.10427460
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into the availability to lucerne (Medicago sativa) of copper applied to yellow-brown pumice soils

Abstract: The relationship between topdressing rate and Cu concentration in lucerne grown on Hinemaiaia sand was investigated using dressings of 0, 0.5, 1, 1.5, 2, and 4 kg Cu/ha. The changes in Cu concentration in the foliage over two years, with three harvests in each, are reported. Differences between years, and among treatments, were significant. In the first year, 4 kg Cu/ha increased the average harvest concentration from 3.6 to 6.7 ppm Cu. In the second year, the effect from 4 kg Cu/ha applied only in year 1, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1978
1978
1989
1989

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Since there is no proven mcthod for mcasuring "availablc" soil Cu in these soils, thc Cu conccntration in luccrne is relatcd to an index of the Cu accumulated from topdrcssing. Forbes (1976) showed that the quantities of EDTAextractablc Cu in the 0--7.5 cm and 7.5-15 cm soil dcpths under "Cu free" pasture on thcse soils were virtually the same. Any concentration above 1 ppm Cu indicates applicd Cu.…”
Section: Methodsmentioning
confidence: 82%
See 4 more Smart Citations
“…Since there is no proven mcthod for mcasuring "availablc" soil Cu in these soils, thc Cu conccntration in luccrne is relatcd to an index of the Cu accumulated from topdrcssing. Forbes (1976) showed that the quantities of EDTAextractablc Cu in the 0--7.5 cm and 7.5-15 cm soil dcpths under "Cu free" pasture on thcse soils were virtually the same. Any concentration above 1 ppm Cu indicates applicd Cu.…”
Section: Methodsmentioning
confidence: 82%
“…The sequence of events in this survey and the field trial of Part II (Forbes 1978) are given in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations